Future Regulation of Partnerships in Poland in the Face of „Traditional Family” Politics - Lewandowska, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article examines the new wave of social issues in the form of informal relationships and confronts it with rather a conservative approach of Polish politicians and their „traditional family politics.” The article tries to analyze whether the current approach and legislative activity is effective or prolongs the inevitable – novelization of the Polish legal system in the scope of recognition of cohabitation. The author recognizes the phenomenon of informal relationships and provides insight into the current state of legal regulation to describe issues beneath it. The author focuses on civil law solutions as they regulate the majority of partnersʼ everyday life. Then discusses the so-called „traditional” approach to the subject of family and relationships by analyzing politiciansʼ public statements axiology of Polish law, the position of the church and regulations proposed for partnerships. Finally, the author confronts it with social expectations arising from the data provided by CBOS and GUS. The analysis provided in the article leads to the conclusion that current politics cannot change the widespread of social phenomena such as partnership, and thus, the legislator must search for new legal solutions.